Long-wave mid-infrared time-resolved dual-comb spectroscopy of short-lived intermediates - Luo, Pei-Ling (Optics letters, 2020)
In this Letter, an electro-optic dual-comb spectrometer with a central tunable range of 7.77-8.22 µm is demonstrated to perform transient absorption spectroscopy of the simplest Criegee intermediate ( ), a short-lived species involved in many key atmospheric reactions, and its self-reaction product via comb-mode-resolved spectral sampling at microsecond temporal resolution. By combining with a Herriott-type flash photolysis cell, can be probed with a detection limit down to ∼1×10 . Moreover, pressure broadening of absorption lines can be studied with spectrally interleaved dual-comb spectroscopy. This Letter holds promise for high-resolution precision measurements of transient molecules, especially for the study of large molecules in complex systems.